Pakistan Distance-Learning Topic Brief: Primary-level Deaf Children - Lynch, Paul; Kaye, Tom; Terlektsi, Emmanouela (EdTech Hub, 2020)
The COVID-19 crisis has severely impacted the ability of national education actors to provide access to education services for all students.This brief provides guidance and recommendations on how to support the education of deaf children in Pakistan using alternative learning approaches. It presents the rationale for adopting certain teaching and learning strategies when supporting the learning and well-being of deaf children during global uncertainty. Children with deafness and hearing loss are particularly vulnerable now that schools are closed. They are isolated at home and unable to access information as easily as when they were attending school. This brief presents some of the practices that are reportedly working well for deaf children in different contexts.
Keywords: C:Pakistan; F: Helpdesk response; L:Special education needs and disabilities (SEND); LP: English; _C:Bangladesh BGD; _C:Ethiopia ETH; _C:India IND; _C:Ireland IRL; _C:Kenya KEN; _C:Pakistan PAK; _C:Rwanda RWA; _C:United Kingdom GBR; _C:United States USA; _DOILIVE; _EdTechHub_Output; _GS:indexed; __C:filed:1; __C:scheme:1; _cover:v1; _r:CopiedFromEvLib; _r:ImportedToMyEducationEvidence; _zenodoETH; docs.opendeved.net; dode_eth-src-eth; dode_eth-trf2-dode